Avaliação dos serviços de pós-graduação lato sensu sob a perspectiva do aluno concluinte para melhoria contínua - Schmitz, Lenice (2006)
This work aims to raise the performance of the courses in post-graduation of lato-sensu level of an Institution of Higher Education by the perspective of the students about to conclude the course, planning to identify possibilities of improvement for the installment of this service and increase new opportunities for the institution. The study was based on a research whose sample was represented by students about to conclude the course. Aspects regarding the context of operation management in services have been analyzed within this purpose. An adaptation of SERVQUAL2 model was used as an instrument, that compares expectations with perceptions of the customers concerning each attribute identified for the service. Also a complementary questionnaire was applied, with questions that have evaluated the general perception of the interviewed concerning the institution's image. From the research, the competitive forces and weaknesses which indicate the main factors that deserve attention of the institution have been detached - besides evaluating items considered, the students have also classified them by relevance order. From the analysis of this information, recommendations are presented so that the managers of the institution take in account the satisfaction of the needs and expectations of the customers, in the long run to guarantee the maintainance of a competitive position of these services.